Students’ Perception on the Use of Cooperative Learning in Writing Activity at State Islamic Senior High School 1 Kuantan Singingi - M Syafii S; Desta Wulandari (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
The aim of this research was to identify the students’ perception on the use of cooperative learning in writing activity at State Islamic Senior High School 1 Kuantan Singingi. This research was descriptive quantitative study. The population of this research was the second year students of State Islamic Senior High School 1 Kuantan Singingi. In this research, the researcher took the sample by using a proportionate stratified random sampling technique. So, the total sample of this research was 119 students consisting of seven classes. Questionnaire was used in order to get the data which is from 4 indicators with 20 items of statements adopted from the study of Kharisma and Hidayati (2018). The result of data analyzed showed that the students’ perception on the use of cooperative learning was at positive category by the percentage 79.8%.